Cervical and anal HPV infection: cytological and histological abnormalities in HIV-infected women in Thailand - Reshmie A. Ramautarsing; Nittaya Phanuphak; Surasith Chaithongwongwatthana; Ferdinand W.N.M. Wit; Nipat Teeratakulpisarn; Tippawan Pankam; Piyanee Rodbamrung; Joep M.A. Lange; Praphan Phanuphak; Vikrant V. Sahasrabuddhe; Stephen Kerr; Jintanat Ananworanich; et al. (Elsevier, 2015)
Background: Women infected with human immunodeficiency virus (HIV) have higher rates of persistent infection with high-risk human papillomavirus (hr-HPV) and cervical and anal dysplasia. We describe the epidemiology of hr-HPV, and cervical and anal intra-epithelial abnormalities in HIV-infected women in Thailand. Methods: HIV-infected women aged 18-49 years, either HAART-naïve or -experienced, were enrolled in Bangkok, Thailand. A demographic and sexual-risk behaviour questionnaire was administered and a pelvic examination with colposcopy was performed on every woman. Cervical and anal samples were tested for cytology and HPV genotyping. Results: A total of 256 women were enrolled with a median [interquartile range (IQR)] age of 35 (32-40) years. Ninety (35.2%) had detectable cervical hr-HPV. Being post-menopausal was associated with increased risk for cervical hr-HPV, while years since HIV diagnosis and plasma HIV RNA <40 copies/mL were significantly associated with decreased risk in multivariable regression analyses. Abnormal cervical cytology was detected in 6.3%. Cervical biopsies that were taken from 99 women (39.3%) owing to abnormalities seen during colposcopy showed cervical intra-epithelial neoplasia (CIN) in 22.6%. The sensitivity of cervical cytology to detect CIN2+ was 10.0%. Among 102 women enrolled in the anal substudy, 18.8% had anal HPV infection and 11.1% had anal hr-HPV. Two women had abnormal anal cytology. Conclusion: We found cervical and anal hr-HPV in 35.2% and 11.1% of Thai HIV-infected women, respectively. Moreover, the observed poor agreement between cervical cytology and histology results could indicate current cervical cancer screening programs for HIV-infected women might not be optimal for the detection of pre-neoplastic lesions.